Fatwa as a Tool of Social Engineering: The Study of Fatwa of Tarjih Muhammadiyah - Mohammad Hasan Bisyri (Jurnal Penelitian, 2020)
This article discusses the function of fatwa, specifically the Tarjih Fatwa in the field of family law. So far, Islamic law is still considered not dynamic and is still limited to only one legal function, which is nahi munkar (social control) yet the function of amar makruf (social engineering) which emphasizes the suggestion to perform good deeds in a general and practical sense is still not optimal. This results in the impression that Islamic law seems to lose its relevance. This article aims to explain the function of Tarjih's fatwa for the community. The study in this article is a literature review using a sociological approach. The results indicated that the law (fatwa) is no longer considered as an independent variable that is separated from other elements, but is a dependent variable, as are social norms and other cultural identities. Tarjih fatwa is aimed at directing society to the desired goals, eliminating inappropriate habits, and creating new patterns of behavior. In other words, the function of Tarjih Fatwa can be used as a means of manipulating society (law as a tool of social engineering).